An evaluation of section 68(1)(b) of the Labour Relations Act 66 of 1995 : how effective is this remedy? - Gericke, S.B. (Ezette) (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2015.